Development of an ABS Nanocomposite Material and Its Application to a Fire-Resistant Glazing System - Part II: Development of a Curtain-Wall-Type Fire-Resistant Glazing System - Kang, Sungwook; Kwon, Minjae; Choi, J. Yoon; Park, Jae Wan (Fire Science and Engineering, 2020)
This study is focused on the development of a curtain-wall-type fire-resistant glazing system to contribute to both energy efficiency and fire safety of a building. The development of an ABS nanocomposite material and its improvement in flammability are presented in Part I (the authors’ companion paper). In this study, the ABS nanocomposite material was scaled up for application to a fire-resistant glazing system in industries. A bench-scale test was designed to quantitatively analyze the frame’s heat transfer performance. To manufacture a pilot model of the glazing system, a glazing part was designed based on numerical simulations of thermal insulation. The performance of the entire glazing system was tested on a full scale in terms of thermal resistance and insulation.